2012
DOI: 10.1088/1367-2630/14/7/073037
|View full text |Cite
|
Sign up to set email alerts
|

Test for bacterial resistance build-up against plasma treatment

Abstract: It is well known that the evolution of resistance of microorganisms to a range of different antibiotics presents a major problem in the control of infectious diseases. Accordingly, new bactericidal 'agents' are in great demand. Using a cold atmospheric pressure (CAP) plasma dispenser operated with ambient air, a more than five orders of magnitude inactivation or reduction of Methicillin-resistant Staphylococcus aureus (MRSA; resistant against a large number of the tested antibiotics) was obtained in less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…Higher plasma powers (0.9 W, 1.6 W) significantly decreased biofilm production by 10 4 MRSA cells regardless of the exposure time ( Fig. 2A), while a decrease in biofilm production by 10 5 MRSA cells required a longer exposure, i.e. 60 and 120 s (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Higher plasma powers (0.9 W, 1.6 W) significantly decreased biofilm production by 10 4 MRSA cells regardless of the exposure time ( Fig. 2A), while a decrease in biofilm production by 10 5 MRSA cells required a longer exposure, i.e. 60 and 120 s (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Most studies have shown very good results [5][6][7][8] in direct contact of plasmas with microorganisms. However sterilization of planktonic samples and biofilms proved to be more difficult [9][10][11][12][13]. In this paper we extend the application of a plasma needle that has been tested in direct contact with plant and mammalian cells [14,15] and for planktonic samples of bacteria [15] to study sterilization of biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…[81] It has been postulated that the accumulation of plasma charged particles over the bacterial cell membrane causes membrane rupture through electrostatic disruption [105] ; or that the reactive species permeabilize and penetrate the cell walls before reacting with DNA via complex mechanisms. [106] Membrane damage through lipid peroxidation is another major cause of bacterial death by CAP. The effect by heat and UV is argued to be indirect or negligible.…”
Section: Mechanisms Of Microbial Inactivation By Capmentioning
confidence: 99%
“…[82] Microorganism resistance to CAP is unlikely to occur. [106] Inexpensive. [202] Can be used portably or in smaller scale (such as in laminar flow hoods and isolators).…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…In contrast to chemical-based technologies, plasmas can be created in environmentally friendly gases, including air, thus minimizing the environmental burden of the technology, and given their broad range of antimicrobial agents it makes it difficult for bacteria to develop resistance. 40 Many of the pioneering studies reported in the literature have used plasma sources initially conceived for other applications (e.g. semiconductor processing).…”
mentioning
confidence: 99%